2020
DOI: 10.3389/fimmu.2020.600127
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Niches and Signals Controlling Immune Cell Development and Maintenance of Immunological Memory

Abstract: Studies over the last couple of decades have shown that hematopoietic stem cells (HSCs) are critically dependent on cytokines such as Stem Cell Factor and other signals provided by bone marrow niches comprising of mesenchymal stem and progenitor cells (MSPCs) and endothelial cells (ECs). Because of their critical roles in HSC maintenance the niches formed by MSPCs and ECs are commonly referred to as HSC niches. For the most part, the signals required for HSC maintenance act in a short-range manner, which impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 176 publications
(219 reference statements)
1
40
0
Order By: Relevance
“…These "MSCs" likely represent heterogeneous stromal subsets rather than bona fide mesenchymal stem cells (101,(122)(123)(124). As mentioned before, all stromal cells may not secrete CXCL12, and PSS cells (sometimes referred to as CXCL12-abundant reticular cells) are one of the main sources of this chemokine in the BM (17,57,65,125). Accordingly, BM PCs were reported to be in close contact with perivascular CXCL12+ stromal cells (57,126,127), but further characterization of this presumed dialogue is still lacking.…”
Section: Plasma Cell Maturation and Maintenance: More Than One Niche?mentioning
confidence: 99%
See 4 more Smart Citations
“…These "MSCs" likely represent heterogeneous stromal subsets rather than bona fide mesenchymal stem cells (101,(122)(123)(124). As mentioned before, all stromal cells may not secrete CXCL12, and PSS cells (sometimes referred to as CXCL12-abundant reticular cells) are one of the main sources of this chemokine in the BM (17,57,65,125). Accordingly, BM PCs were reported to be in close contact with perivascular CXCL12+ stromal cells (57,126,127), but further characterization of this presumed dialogue is still lacking.…”
Section: Plasma Cell Maturation and Maintenance: More Than One Niche?mentioning
confidence: 99%
“…Several niche factors have been reported to provide HSCs with instructive clues to regulate their location, retention, self-renewing, and fate (57,(61)(62)(63)(64)(65). In particular, Stem Cell Factor (SCF) and CXCL12 are required for HSC maintenance and retention in the BM (17,63,66,67). PSS cells identified by surface expression of the Leptin receptor (LepR) promote HSC maintenance and the use of knock-in mouse models showed that these cells are the main source of SCF and CXCL12 (31,57,62,63,(67)(68)(69).…”
Section: Hsc and Mpp Niches: Distinct Or Shared?mentioning
confidence: 99%
See 3 more Smart Citations